A prime decomposition algorithm for supercodes - Kieu, Hung Van (Journal of Computer Science and Cybernetics, 2013)
<!–[if gte mso 9]> <![endif]–>Supercode, a particular case of hypercodes, has been introduced and considered by D. L. Van and the author in previous papers. A supercode is called prime if it cannot be decomposed as a catenation of two supercodes. The prime decomposition of a supercode L is to decompose L into prime supercodes. In this paper, a linear-time prime decomposition algorithm for supercodes is proposed. The uniqueness of the prime decomposition for supercodes is presented. <!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; –> <!–[endif] –>